Analysis of the bacterial community from high alkaline (pH > 13) drainage water at a brown mud disposal site near Žiar nad Hronom (Banská Bystrica region, Slovakia) using 454 pyrosequencing - Kisková, Jana; Stramová, Zuzana; Javorský, Peter; Sedláková-Kaduková, Jana; Pristaš, Peter (Folia microbiologica, 2019)
Brown mud, as a waste product of the industrial process of aluminum production, represents a great environmental burden due to its toxicity to living organisms. However, some microorganisms are able to survive in this habitat, and they can be used in bioremediation processes. Traditional cultivation methods have a limited capacity to characterize bacterial composition in environmental samples. Recently, next-generation sequencing methods have provided new perspectives on microbial community studies. The aim of this study was to analyze the bacterial community in the drainage water of brown mud disposal site near Žiar nad Hronom (Banská Bystrica region, Slovakia) using 454 pyrosequencing. We obtained 9964 sequences assigned to 163 operational taxonomic units belonging to 10 bacterial phyla. The phylum Proteobacteria showed the highest abundance (80.39%) within the bacterial community, followed by Firmicutes (13.05%) and Bacteroidetes (5.64%). Other bacterial phyla showed an abundance lower than 1%. The classification yielded 85 genera. Sulfurospirillum spp. (45.19%) dominated the bacterial population, followed by Pseudomonas spp. (13.76%) and Exiguobacterium spp. (13.02%). These results indicate that high heavy metals content, high pH, and lack of essential nutrients are the drivers of a dramatic reduction of diversity in the bacterial population in this environment.
Keywords: Biodiversity; High alkalinity; chemické látky znečišťující vodu; Heavy metals; Biodegradation, Environmental; Slovakia; Slovenská republika; fylogeneze; Metallurgy; High-Throughput Nucleotide Sequencing; RNA, Ribosomal, 16S; těžké kovy; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; biodiverzita; Bacteria; odpadní voda; Water Pollutants, Chemical; Bacterial Physiological Phenomena; Hydrogen-Ion Concentration; Waste Water; Brown mud; Microbial Consortia; 454 pyrosequencing; koncentrace vodíkových iontů; mikrobiální společenstva; vysoce účinné nukleotidové sekvenování; Drainage water; RNA ribozomální 16S; Metals, Heavy; hutnictví; Wastewater; biodegradace; fyziologie bakterií